Gallic acid suppresses the progression of triple-negative breast cancer HCC1806 cells via modulating PI3K/AKT/EGFR and MAPK signaling pathways - Lin, Si; Qin, Hui-Zhen; Li, Ze-Yu; Zhu, Hua; Long, Li; Xu, Li-Ba (Frontiers in Pharmacology, 2022)
Triple-negative breast cancer (TNBC) is a severe threat to women's health because of its aggressive nature, early age of onset, and high recurrence rate. Therefore, in this study, we aimed to evaluate the anti-tumor effects of Gallic acid (GA) on the TNBC HCC1806 cells in vitro. The cell proliferation was detected by MTT and plate clone formation assays, cell apoptosis, cell cycle, and mitochondrial membrane potential (MMP) were analyzed by flow cytometry and Hoechst 33258 staining assays, and the intracellular reactive oxygen species (ROS) accumulation were also investigated. Real-Time PCR and western blot were examined to explore the mechanism of action. The results indicated that GA suppressed HCC1806 cells proliferation and promoted HCC1806 cells apoptosis. Meanwhile, GA treatment changed the morphology of the HCC1806 cells. In addition, GA blocked the HCC1806 cells cycle in the S phase, and it induced cells apoptosis accompanied by ROS accumulation and MMP depolarization. Real-Time PCR results suggested that GA increased Bax, Caspase-3, Caspase-9, P53, JINK and P38 mRNA expression, and decreased Bcl-2, PI3K, AKT and EGFR mRNA expression. Western blotting results suggested that GA increased Bax, cleaved-Caspase-3, cleaved-Caspase-9, P53, ERK1/2, P-JNK, P-P38 proteins expression, and decreased Bcl-2, P-PI3K, P-AKT, P-EGFR proteins expression. Furthermore, molecular docking suggested that GA has the high affinity for PI3K, AKT, EGFR, ERK1/2, JNK and P38. In conclusion, GA could suppress HCC1806 cells proliferation and promote HCC1806 cells apoptosis through the mitochondrial apoptosis pathway and induces ROS generation which further inhibits PI3K/AKT/EGFR and activates MAPK signaling pathways. Our study will provide some new references for using GA in the treatment of TNBC.